Interleukin (IL)-1β and IL-10 Host Responses in Patients With Staphylococcus aureus Bacteremia Determined by Antimicrobial Therapy. (31st July 2019) - Volk, Cecilia F; Burgdorf, Sarah; Edwardson, Graham; Nizet, Victor; Sakoulas, George; Rose, Warren E
Abstract: Background: Patient interleukin (IL)-1β and IL-10 responses early in Staphylococcus aureus bacteremia (SaB) are associated with bacteremia duration and mortality. We hypothesized that these responses vary depending on antimicrobial therapy, with particular interest in whether the superiority of β-lactams links to key cytokine pathways. Methods: Three medical centers included 59 patients with SaB (47 methicillin-resistant S. aureus [MRSA], 12 methicillin-sensitive S. aureus [MSSA]) from 2015–2017. In the first 48 hours, patients were treated with either a β-lactam (n = 24), including oxacillin, cefazolin, or ceftaroline, or a glyco-/lipopeptide (n = 35), that is, vancomycin or daptomycin. Patient sera from days 1, 3, and 7 were assayed for IL-1β and IL-10 by enzyme-linked immunosorbent assay and compared using the Mann-Whitney U test. Results: On presentation, IL-10 was elevated in mortality ( P = .008) and persistent bacteremia ( P = .034), while no difference occurred in IL-1β. Regarding treatment groups, IL-1β and IL-10 were similar prior to receiving antibiotic. Patients treated with β-lactam had higher IL-1β on days 3 (median +5.6 pg/mL; P = .007) and 7 (+10.9 pg/mL; P = .016). Ex vivo, addition of the IL-1 receptor antagonist anakinra to whole blood reduced staphylococcal killing, supporting an IL-1β functional significance in SaB clearance. β-lactam–treated patients had sharper declines in IL-10 than vancomycin or daptomycin –treated patients over 7 days. Conclusions: These data underscore the importance of β-lactams for SaB, including consideration that the adjunctive role of β-lactams for MRSA in select patients helps elicit favorable host cytokine responses. Abstract : In this study, we evaluate the host cytokines interleukin (IL)-1β and IL-10 response in the first 7 days of Staphylococcus aureus bacteremia (SaB) treatment. β-lactam therapy resulted in a more favorable host response, underscoring the importance of using β-lactams whenever possible for SaB, including select methicillin-resistant S. aureus patients to help elicit favorable host cytokine response profiles.